The Historical Narrative in the Abbasid Era in Light of Ibn al-Faqih's "Kitab al-Buldan" (d. approx. 334AH/956) Comparative Study - Dr. Dina Abd Alsadah Rasan (Journal of College of Education, 2026)
Books of countries are among the works that highlight geographical and field details, making them an important source in this regard. It is also no secret to esteemed researchers that they contain significant historical information that cannot be overlooked due to its importance. They resemble travel memoirs through which we discover those countries and cities and the changes time has wrought upon them. Thus, these books serve as a strong link between the past and present of cities, bearing witness to the life of humans who dedicated their lives to development and urban planning. Each city was known for its architectural artistry, rivers, and streets. Consequently, books of countries were not merely the journey of a specific scholar but rather a historical, visual, and sensory testimony to every city—a rich record of urban and historical exploration.
Keywords: Narrative, Historical, in, Ibn al-Faqih Al-Hamadhani